Genetic, textual, and archeological evidence of the historical global spread of cowpea (Vigna unguiculata [L.] Walp.). Issue 4 (26th August 2020) - Herniter, Ira A.; Muñoz‐Amatriaín, María; Close, Timothy J.
Abstract: Cowpea ( Vigna unguiculata [L.] Walp.) was originally domesticated in sub‐Saharan Africa but is now cultivated on every continent except Antarctica. Utilizing archeological, textual, and genetic resources, the spread of cultivated cowpea has been reconstructed. Cowpea was domesticated in Africa, likely in both West and East Africa, before 2500 BCE and by 400 BCE was long established in all the modern major production regions of the Old World, including sub‐Saharan Africa, the Mediterranean Basin, India, and Southeast Asia. Further spread occurred as part of the Columbian Exchange, which brought African germplasm to the Caribbean, the southeastern United States, and South America and Mediterranean germplasm to Cuba, the southwestern United States, and Northwest Mexico.